Laboratory digital signal analysis with virtual spectrum analyzer - Hengkietisak, Siriporn; Tipyakanont, Surapol; Tangsiriworakul, Chanwit; Manop, Chalermchat; Senavongse, Wongwit (My University, 2005)
This paper present laboratory digital signal analysis with virtual spectrum analyzer which is created using LabVIEW program on digital oscilloscope TDS 5054. This research aims to develop a knowledge-base on digital signal analysis and the working of virtual instrumentation, a topic which is currently attracting wide interest due to its many good attributes including flexibility, modularity, and low cost. It also aims to make a good use of expensive digital oscilloscope TDS 5054. In this study, laboratory spectrum analysis is performed with variable sampling rate, effect of windows filter etc. The results are displayed by both time domain and frequency domain. There are samples of signal waveforms such as Sinusoidal Waveform, Square waveform, Six-step waveform, and PWM (pulse width modulation) waveform. These waveforms are important in the study of power electronics. The data are obtained using special module program to extract information from the digital oscilloscope. © 2005 IEEE.
Keywords: Laboratory signal processing; LabVIEW; Virtual instrument